Polychlorinated biphenyl (PCB) alterations of antioxidant defenses and xenobiotic metabolism in teleost fish: Role of tissue glutathione metabolism in xenobiotic detoxication pathways. - Otto, Diana M. E. (University of Ottawa (Canada), 1996)
Polychlorinated biphenyls (PCBs) are ubiquitously distributed in the aquatic and terrestrial environments, even though their production was stopped more than 20 years ago. The biochemical effects of PCBs are primarily initiated by the induction of drug metabolizing enzymes, especially cytochromes P450. In the first instance, these enzymes detoxify xenobiotics such as PCB congeners to facilitate their excretion from the animal. However, these processes are also known to generate more toxic metabolites, including the production of reactive oxygen species (ROS) which impact on cellular antioxidant defenses. Teleost fish contain an active endogenous antioxidant defense system, which consists of superoxide dismutase, catalase and the glutathione system. Apart from its antioxidant functions, glutathione (GSH) plays a major role in electrophilic conjugation of lipophilic conjugation (initiated by glutathione S-transferase, GST) and in the maintenance of cellular homeostasis. This thesis investigated the responses of drug metabolizing enzymes and endogenous antioxidant defenses in teleosts exposed to PCBs. The first field study showed that feral brown bullheads, harvested from the St. Lawrence River and contaminated with PCBs, had enhanced activities of ethoxyresorufin O-deethylase (EROD), a cytochrome P4501A (CYP1A) catalytic activity. GST activities were induced several fold in these River bullheads, which suggested active detoxication via GSH conjugation, although at the expense of tissue GSH content. A second field study involved the caging of hatchery reared rainbow trout at a PCB contaminated site. The trout showed significant accumulation of PCB congeners in skeletal muscle in the absence of changes in tissue drug metabolizing enzymes and antioxidant defenses. Endogenous antioxidant defenses were examined in rainbow trout and black bullheads. These systems were found to underlie age- and/or maturation-dependent changes. In a series of experiments, exogenous GSH was noted to serve as an efficient delivery agent of GSH to tissues in teleosts. This observation suggests that piscine GSH biochemistry differs from that of mammals, which respond poorly to exogenous GSH. This unique characteristic of the piscine GSH system could be important for fish husbandry while providing an interesting tool to study the biochemical effects of PCBs. A series of experiments found that a 3 day exposure of rainbow trout to 3,3$\sp\prime$,4,4$\sp\prime$-tetrachlorobiphenyl (TCB) had little impact upon tissue antioxidant defenses, while a 6 week exposure resulted in significant induction of activities of the conjugation enzyme UDP-glucuronosyltransferase, antioxidant enzymes activities and GSH levels in hepatic and extrahepatic tissues. However in both experiments TCB induced CYP1A metabolism. Additional experiments attempted to characterize to what extent tissue glutathione status influences basal and TCB induced hepatic CYP1A metabolism. Manipulation of tissue GSH content by either depletion (induced by L-buthionine- (S,R) -sulfoximine, BSO) or supplementation with pro-GSH agents (GSH and lipoate) revealed that glutathione status modified cytochrome P4501A at two stages, the CYP1A mRNA expression and the catalytic activity. This apparent cross-talk between the glutathione and cytochrome P450 systems suggested that glutathione homeostasis plays a major role in PCB induced metabolic alterations.
Keywords: Health Sciences, Toxicology.